KERUSAKAN TEGAKAN TINGGAL AKIBAT KEGIATAN PENEBANGAN DAN PENYARADAN: KASUS DI SUATU PERUSAHAAN HUTAN DI RIAU - Sona Suhartana; Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1994)
This paper presents study results  of residual  stand damages caused by felling and  skidding activities.  The case study was  carried out at PT Dwi Marta in Riau in 1993.  The aims are : (1) tofind  the impact of felling and skidding on residual stand damages, (2) to know the factors  influencing the residual  stand  damages  and (3) tofind  the way of  reducing residual stand damage.Data on the number of trees with diameter 20 cm and up,   trees damages were collected.  The data  was analised  by  using themultiple regression.The result of study shows :1.The residuol stand damage caused by felling ranged between 2.7-10. 6% with an average of  6.6%/ha.2.The residual stand damage caused by skidding with crawler tractor  varied from  2. 7% to 22.3% with an average of 12. 7%ha.3.Both the number of  trees felled  and the  slope in had highly significant effect  to residual stand  damages. The greater  the  number of  trees felled  and  the slope, the greater the residual stand  damages.